2014
DOI: 10.1111/eea.12224
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mating patterns on reproductive performance and offspring fitness in Cryptolaemus montrouzieri

Abstract: We examined the female mating choice of Cryptolaemus montrouzieri Mulsant (Coleoptera: Coccinellidae) when exposed to a male with which she had mated before vs. a novel male which she never encountered. After first mating, most females chose to remate with the same male and showed a shorter mating latency period to copulation with the familiar male as compared to a new male. Then, we allowed a female to mate once, 59 with the same, or 59 with different males to evaluate how different mating patterns influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…The results of the third experiment revealed that females of H. variegata preferred familiar males over unfamiliar males and preferred to re-mate quickly with them. These results are consistent with the studies on Cryptolaemus montrouzieri Mulsant (Coleoptera: Coccinellidae) (Jiaqin et al 2014); Tenuis valvaenotata (Mulsant) (Coleoptera: Coccinellidae) (Túler et al 2018) and cabbage beetle, Colaphellus bowringi (Baly) (Coleoptera: Chrysomelidae) (Liu et al 2010), where females prefer to remate with familiar males.…”
Section: Treatmentsupporting
confidence: 91%
See 1 more Smart Citation
“…The results of the third experiment revealed that females of H. variegata preferred familiar males over unfamiliar males and preferred to re-mate quickly with them. These results are consistent with the studies on Cryptolaemus montrouzieri Mulsant (Coleoptera: Coccinellidae) (Jiaqin et al 2014); Tenuis valvaenotata (Mulsant) (Coleoptera: Coccinellidae) (Túler et al 2018) and cabbage beetle, Colaphellus bowringi (Baly) (Coleoptera: Chrysomelidae) (Liu et al 2010), where females prefer to remate with familiar males.…”
Section: Treatmentsupporting
confidence: 91%
“…2008; Michaud et al 2013;Jiaqin et al 2014;Mirhosseini et al 2014;Colares et al 2015;McDonald and Pizzari 2016) and females tend not to copulate with recently mated males (Markow et al 1978;Nakatsuru and Kramer 1982;Gerofotis et al 2015).…”
Section: Treatmentmentioning
confidence: 99%
“…Regarding the effects of multiple mating on females’ survival, we expected that polygynandrous females would live longer than once-mated females, possibly due to the acquisition of nutritional benefits from seminal fluid obtained through multiple mating. In some insect species, benefits may accrue through male offering spermatophores or nuptial gifts during courtship and copulation (Michaud et al , 2013; Jiaqin et al , 2014; Colares et al , 2015). In contrast, our results showed that for T. notata this is not the case.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it is well recognized that male insect ejaculates may variously affect females, including acceleration of oviposition rate, increases in fecundity and fertility, and other subtle paternal effects (Gillott, 2003; Avila et al , 2011). In this context, some authors have suggested that if a male's investments in seminal fluid are high, young and virgin males could better boost female's fitness compared with older and previously mated males (Michaud et al , 2013; Jiaqin et al , 2014; Mirhosseini et al , 2014; Colares et al , 2015; McDonald & Pizzari, 2016). Thus, females would be expected to recognize and choose younger virgin males to maximize their fitness.…”
Section: Introductionmentioning
confidence: 99%
“…The wax secretions and honeydew produced by mealybugs act as both attractants and oviposition stimulants for C. montrouzieri females (Merlin et al, 1996), which are able to lay viable eggs as long as they can prey on mealybugs (Finlay-Doney and Walter, 2012). A single adult female lays about 400 eggs in 40 days of oviposition (Babu and Azam, 1987;Siddhapara et al, 2013) and this quantity can increase if multiple mating occurs (Xie et al, 2014).…”
Section: Introductionmentioning
confidence: 99%